Evaluation of Village Information System Maturity Using the KAMI Index: A Case Study of Indraloka Mukti Village and Its Significance in Information Security Readiness - Firmansyah Tri Wahyudi; Muhammad Said Hasibuan (Dinasti International Journal of Education Management And Social Science, 2024)
Information systems are important in managing village data and information, including population data, correspondence administration, and other public services. One of the villages that implemented an information system is Indraloka Mukti village in the Way Kenanga sub-district, Tulang Bawang Barat district. With the implementation of information technology, various risks emerge that can threaten the security of information systems. Considering the importance of information systems in village operations, it is necessary to identify, evaluate, and manage risks to existing information systems. The measuring tool in this research is the KAMI Index (Information Security). The results of the assessment of information security readiness in Indraloka Mukti Village using the KAMI Index show that the electronic system received a score of 17 and is included in the "High" Category; Information security received a score of 90 out of 645, falling within the "Inadequate" Level of Readiness to meet ISO/IEC 270001 standards. All parts of the information security system must be updated, with the lowest maturity level at Level I and the highest at level I+.